2013
DOI: 10.1007/s12039-013-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Mannich reaction: A versatile and convenient approach to bioactive skeletons

Abstract: This review gives an insight into the recent applications of Mannich reaction and its variants in the construction of bioactive molecules. Emphasis is given to the Mannich reaction that provides bioactive molecules and/or modifies the property of an existing bioactive molecule. The role of Mannich reaction in the construction of antimalarial, antitumour, antimicrobial, antitubercular, antiinflammatory and anticonvulsant molecules and also the significance of aminoalkyl Mannich side chain on the biological prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 62 publications
0
46
0
1
Order By: Relevance
“…The chemistry of Mannich bases has been the subject of wide and increasing interest, due to their biological activities such as analgesic, antimalarial, anticonvulsant, antipsychotic, cytotoxic, antiinflammatory, and antimicrobial activities [3][4][5]8,9,[17][18][19][20][21][22] . In addition, the Mannich bases of several bioactive molecules such as Taxol (anticancer agent), SCH48461 (anticholesterol agent), Tramadol (analgesic), Osnervan (antiparkinson), and Moban (neuroleptic) were prepared and they showed increased bioactivities comparing to the parent compounds 23 . Doxorubicin causes multidrug resistance in tumor cells but the synthetic Mannich base analog of Doxorubicin showed signiEcant activity against multi drug-resistant tumor cell lines 23 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemistry of Mannich bases has been the subject of wide and increasing interest, due to their biological activities such as analgesic, antimalarial, anticonvulsant, antipsychotic, cytotoxic, antiinflammatory, and antimicrobial activities [3][4][5]8,9,[17][18][19][20][21][22] . In addition, the Mannich bases of several bioactive molecules such as Taxol (anticancer agent), SCH48461 (anticholesterol agent), Tramadol (analgesic), Osnervan (antiparkinson), and Moban (neuroleptic) were prepared and they showed increased bioactivities comparing to the parent compounds 23 . Doxorubicin causes multidrug resistance in tumor cells but the synthetic Mannich base analog of Doxorubicin showed signiEcant activity against multi drug-resistant tumor cell lines 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Mannich bases of several bioactive molecules such as Taxol (anticancer agent), SCH48461 (anticholesterol agent), Tramadol (analgesic), Osnervan (antiparkinson), and Moban (neuroleptic) were prepared and they showed increased bioactivities comparing to the parent compounds 23 . Doxorubicin causes multidrug resistance in tumor cells but the synthetic Mannich base analog of Doxorubicin showed signiEcant activity against multi drug-resistant tumor cell lines 23 . The introduction of aminoalkyl Mannich side chain into Topotecan increased the water solubility of this anticancer agent 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lorand et al studied the antimicrobial properties of unsaturated Mannich ketones and he found that the presence of Mannich side chain increase the water solubility of unsaturated Mannich ketones [11][12].…”
Section: Antimicrobial Property Of Mannich Basesmentioning
confidence: 99%
“…Mannich base is a b-amino-carbonyl compound, which is formed in the reaction of an amine (primery or secondary), formaldehyde and a reactive hydrogen atom 29 . Mannich bases have been reported to be useful agent for potential biological activities such as anticancer, antibacterial, antifungal, analgesic, antiinflammatory, antimalarial and antitubercular 30 . Many Mannich bases of 1,2,4-triazoles carrying N-methylpiperazine moiety are reported to possess protozoacidal and bactericidal activities 31 .…”
Section: Introductionmentioning
confidence: 99%